Influence of Principals’ Collaborative Practices on Students’ Performance in Secondary Schools in Murang’a and Kirinyaga Counties, Kenya - Cecilia Irungu; Josphat Kagema; Michael Gachahi (STAI Miftahul Ula Nganjuk, 2019)
Despite the fact that Kenyan children have more opportunities to attend school, there still remains large gaps in learning outcomes. This stagnation in learning is confirmed by results of national examinations including Kenya Certificate of Secondary Education (KCSE). According to KCSE examinations results analysis, performance in secondary schools in different parts of Kenya is still below expectations and this trend is worrying. The number of students in Murang’a and Kirinyaga Counties who have continuously scored grade D+ and below every year have consistently remained high compared to those attaining university minimum admission grade of C+ and above. This low performance has persisted despite most schools having adequate and well trained teachers as well as adequate facilities. This study examined the influence of principals’ collaborative practices on students’ performance in Murang’a and Kirinyaga Counties, Kenya. The study involved a sample of 205 principals and 367 teachers selected from 436 secondary schools in the two counties. The researchers used validated questionnaires and interview schedules to collect data from teachers and principals respectively. Data was analysed using both descriptive and inferential statistics. The study established that principals’ promotion of collaborative practices was higher in Kirinyaga than in Murang’a County. It was noted that secondary schools in Kirinyaga County post better results in KCSE than those in Murang’a County and the study concluded that collaborative practices enhanced academic performance. This study recommended that principals should promote collaborative practices in their schools. This can be done through engaging stakeholders in networking and linkages that promote collaboration and can lead to better academic performance.